Wear characterization by oil analysis in automatic and manual bus engine gearbox / Norhanifah Abdul Rahman - Abdul Rahman, Norhanifah (2015)
In Malaysia, public transportation has become the main way for citizen to go from one place to another. One of the popular and yet the very important ways of public transportation is the bus. Ease of availability, cheap and fast were the reasons why people choose bus in comparison to other means of public transport. In order to maintain the bus life span so that it can be used for a long time without any major problem; the bus should be maintained and serviced according to its mileage usage.Thus, this research focuses on the analysis of transmission fluid sample by using experimental approach after a certain mileage. The objectives of this work are to collect the oil sample from automatic and manual transmission systems of engine bus according to manufacturer's recommendations, to analyse collected oil sample using oil analysis technique i.e. ferrographic, FTIR, AES and to predict the wear morphology, spectral outcomes and wear element concentration from the oil analysis results. The sample transmission fluid which was taken from the automatic and manual transmission gearbox has been experimentally analyzed. The oil sample were taken with an interval of 5,000km, 30,000km, 50,000km, 80,000km, 180,000km and 300,000km for automatic transmission bus operation, and 5,000km, 50,000km, 100,000km, 150,000km and 200,000km for manual transmission bus operation. This sample then has been analyzed by comparing between new and used transmission fluid using FM-III Ferrogram Maker, FTIR and spectrometer. Oil analysis by ferrographic, FTIR and spectrometric technique is a form of Predictive Maintenance (PdM) to avoid major failure in machine elements. Most machine elements are not easily accessible in the transmission system. Having a reliable technique would avoid the needs to open the components unnecessarily, hence, help to prevent catastrophic failure which are very costly, and ease of regular monitoring. In order to identify the major failures of automatic gearbox, forecasts can be made regarding the lube transmission fluid analysis test. By using these test, the minor problem can be determine before become into major failures. At the end of this research, the wear particles profile for interval mileage of automatic and manual transmission system were obtained